Dermatological Examination Training: Shaping Careers Through Hands-On Practice - Didina-Catalina Barbalata; Cristian Toma (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Choosing a career path represents a decision of immense significance in the lives of aspiring medical professionals and is influenced by several pivotal factors such as: clinical exposure, hands-on experience and interaction with specialists in the field. Dermatology represents one speciality in which hands-on experience is crucial and medical simulation training can ensure an innovative and transformative tool to develop the skills needed for dermatological evaluation. AIM: Our research explores the impact of participating in hands-on dermatological evaluation training on the decision to pursue a career path within this field. By analyzing the participants' views regarding the training, their skill self-assessment and the objective evaluation of theoretical knowledge, we aim to analyze how this type of workshop shapes professional goals. METHODS: We conducted a single-center analysis on the training experience of 50 medical students, divided in groups of ten. The training, conducted by a dermatologist, consisted of 1-hour theoretical presentation and 3-hour bedside practice, the students examining each other alternately. A ten questions knowledge assessment questionnaire was used to evaluate the participants before and after the workshop. Additionally, the students were  surveyed regarding their views on the impact of this training on their decision to pursue a career in dermatology and the self-assessment pre- and post-training on a five-point Likert scale. RESULTS: We observed a 48% increase in the knowledge assessment scores (before: 5.26±1.33 out of 10, after: 7.8±0.88 out of 10). A similar increase was observed in the participants' self-assessment scores, as they doubled (before: 1.76+/-0.62 out of 5, after: 3.84+/-0.88 out of 5). Although 60% of the participants were not interested in pursuing a career in dermatology before the training, the hands-on experience determined 64% to take this speciality into consideration as a potential career path. Unanimously, the participants agreed that this training represents a valuable addition to the classical clinical curriculum as it allows hands-on practice which could improve their confidence in the future patient interactions. CONCLUSION: In summary, our research highlights the importance of integrating hands-on training into medical education to better prepare students for their roles in healthcare and adapt to evolving medical practices.